PENGARUH AGRESIVITAS PAJAK DAN MEDIA EKSPLOSURE TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Winda Plorensia A.P; Pancawati Hardiningsih (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
This study aims to examine the effect of the tax aggressiveness and eksplosure media company with its corporate social resposibity ( CSR ). This research was conducted in the mining company listed on the Indonesia Stock Exchange.CSR indicates that corporate responsibility should be based on the triple bottom line of a company's social responsibility , environmental , and financial . Sample were obtained by using pooled time series as many as 68 companies from 2011-2014 . Data collection methods used in this study is a content analysis of social disclosure in the annual report of the company. The use of statistical methos in this research is multiple regression. The results of this study indicate that the tax aggressiveness positive significant effect on CSR , while media eksplosure positive significant effect on CSR . Companies that have a high rate of profit then inclined to make greater disclosure of CSR . CSR communicating through the media will enhance the company's reputation in the eyes of the public in accordance.  Keywords: corporate social responsibiltiy,tax aggressiveness,media eksplosure.